State-of-the-Art Theories and Empirical Evidence Selected Papers from the 6th International Conference on Governance, Fraud, Ethics, and Social Responsibility (Springer Singapore, 2018)
This book discusses several important issues related to corporate governance reporting, corporate social responsibility (CSR), fraud and bankruptcy. It gathers papers presented at the 6th International Conference on Governance, Fraud, Ethics and Social Responsibility, which was held in Penang, Malaysia on 18-19 November 2015. The content is divided into three major sub-themes: Corporate Governance and Accountability; Corporate Social Responsibility (CSR) and Sustainable Development; and Ethics, Risk and Fraud. The first sub-theme addresses recently identified issues, such as corporate governance reporting, corporate governance regulation differences between countries, governance and financial market economics, financial market supervision, and control and risk management. In turn, the second sub-theme focuses on international auditing standards, green/socially responsible investment, environmental and social accounting and auditing, CSR-related matters, legislation and CSR reporting differences for public listed companies, accounting for sustainable development performance, and sustainability assessment models. The third sub-theme puts the spotlight on financial assessment and diagnosis, modeling, hedging, fraud, bankruptcy, accounting and auditing ethics and ethical problems in financial markets. Taken together, the issues discussed here provide state of art theories and empirical evidence approached from broad perspectives, making the book a valuable resource for researchers, students and practitioners alike.